Experimental characterization of the moment-angle curve during level and slope locomotion of transtibial amputee: Which parameters can be extracted to quantify the adaptations of microprocessor prosthetic ankle?. (July 2021) - Davot, Julie; Thomas-Pohl, Marie; Villa, Coralie; Bonnet, Xavier; Lapeyre, Eric; Bascou, Jospeh; Pillet, Hélène
In case of transtibial amputation, the deficit resulting from the loss of the lower limb can be partly compensated with a prosthetic foot and adapted rehabilitation. New prosthetic feet have been developed for transtibial amputees to mimic ankle adaptability to varying terrain. Among them, Microprocessor Prosthetic Ankles (MPA) have a microprocessor to control an electric or a hydraulic actuator to adapt ankle kinematics in stairs and slopes. The objective is to investigate parameters extracted from the moment-angle curve (MAC) and use them to compare 3 MPA during level and slope locomotion against energy storing and return (ESR) foot. Five persons with lower limb transtibial amputation successively fitted with 3 MPA (Propriofoot™, Elan™, Meridium™) compared to their ESR foot. The participants had 2 weeks of adaptation before data acquisition and then a 3 week wash-out period. Range of motion, equilibrium point, hysteresis, late stance energy released, and quasi-stiffness were computed on level ground and 12% slope (upward and downward) thanks to the MAC at the ankle. The study shows the relevance of MAC parameters to evaluate the behavior of MPA. In particular, compared to ESR, all MPA tested in the present study demonstrated a better angle adaptation between walking conditions but a decrease of available energy for the propulsion. Among MPA, main results were: (i) for the Propriofoot™: an adaptation of the ankle angle without modification of the pattern of the MAC (ii) for the Elan™: a limited adaptation of the range of motion but a modification of the energy released (iii) for the Meridium™, the highest adaptation of the range of motion but the lowest available energy of propulsion. One of the main findings of the research is to show and quantify the relationship between range of motion and energy available when using different prosthetic feet in different walking conditions.